3D carbon framework-supported FeSe for high-performance potassium ion batteries. Issue 9 (27th July 2020) - Deng, Jianhua; Huang, Xianglong; Gao, Wei; Liu, Hongdong; Xu, Maowen
Abstract : FeSe@C with a 3D porous interconnected carbon framework is used as the anode for potassium ion batteries (PIBs). Abstract : FeSe@C with a 3D porous interconnected carbon framework is used as the anode for potassium ion batteries (PIBs). FeSe@C has a relatively large specific surface area and a superior microporous and mesoporous structure, thus facilitating the storage and transportation of potassium ions. When tested in PIBs as an anode, FeSe@C shows good specific capacity of 298.5 mA h g −1 after 200 cycles at 500 mA g −1, thus indicating good cycle stability. In addition, a possible potassium storage mechanism is explored. Moreover, the diffusion coefficient of potassium ions ( D K ) of FeSe@C is 1.67 × 10 −10 cm 2 s −1 is calculated. Therefore, the FeSe@C composite is expected to become the next-generation anode material for PIBs.